PENGAJIAN MELAYU DAN MASA DEPAN: KEPERLUAN MEMBANGUN NARATIF BARU - Khaled Nordin, Mohamed (JURNAL MELAYU SEDUNIA, 2020)
Malay Studies is a discipline that has long existed not only in Malaysia, but has had historical roots with institutions overseas, particularly in the Netherlands and the United Kingdom. This development was influenced by the history of imperialism in Europe. In the changing times and modernity, the development of this field of knowledge is declining in the west as the importance of imperialism begins to fade. Now it is time for Malaysia to reexamine the Malay studies’ current position, building the need to develop a new narrative in accordance with the development of technology and globalization. The various developments taking place in the world is not only changing the methodology and knowledge of Malay studies in Europe, but also the landscape and situation of Malay Studies in Malaysia. It is necessary for dynamic changes to be made to ensure that this field of knowledge remains relevant to the modern era and situation in Malaysia. In line with this step, the Johor State Government has also taken accountability and not just rely on universities and academia through a master plan to empower the Malay culture. This is consistent with the goal of making the state of Johor as a field of study and equally uphold the field of Malay studies in the region.